Architecture styles and their impact on the traditional building in the light of contemporary building technology in the city of Karbala: case study” separate residential neighborhoods” - Alzurfi, Hawraa (Al-Adab Journal, 2025)
The research dealt with architectural styles and their impact on the building’s residents in light of technological development, especially after the events of 2003 AD.The planning and urban studies paid great attention and direction in the study of the city’s architecture and its urban style, and one of the most famous features of civilization stands out, which is any country, and from us I do not doubt that the styles of architecture have a fragrant personality and a distinct personality, but we notice a clear clarity between what is between thought as a personality, which is the city and between Its modern architecture, as the Karbala architecture entered a new phase, as is the case of any other architecture, as a result of variations, including the blind expectation of everything that is new and modern in the building without returning to contact with the thought of architecture and its civilizational characteristics and its connection with the next general thought, and abandoning our heritage and culture and walking and immersion under the name of globalization and development thus, we become without an identity or heritage which led to the emergence of extraneous architecture styles that do not agree and master with architecture. The city is urban, and then it became a mere transfer to the production of these modern technologies without trying purely in favor of the existence of a kind of tampering and clearly visible visual distortion on the city’s urbanization and its morphological witness. This requires drawing up a special policy for organizing buildings in accordance with applicable urban legislation and in a way that achieves prospects for foreseeable urban development.